Prevalence Of Polycystic Ovary Syndrome Among Reproductive Age Women: A Rural Based Cross Sectional Study - Devi, Sapam Debika; Paul, Talagatoti David Ratna (Journal of Neonatal Surgery, 2025)
Introduction: Polycystic ovary syndrome (PCOS) affects 5–13% of reproductive-aged women, leading to reproductive, metabolic, and psychological challenges. Complications like gestational diabetes and hypertension are common in affected women. This study aims to assess the prevalence and associated factors of PCOS among reproductive-aged women, enhancing awareness and improving management through targeted interventions. Materials and Methods: This study employed a quantitative, descriptive cross-sectional design in Gautam Budha Nagar, Greater Noida, targeting women aged 15–49 years. A sample of 100 women was selected through convenience sampling. Inclusion criteria included reproductive-aged women, while pregnant or breastfeeding women and those with other androgen excess conditions were excluded. A self-structured questionnaire assessed PCOS symptoms and demographic factors. Data analysis involved descriptive and inferential statistics. Results: Of the participants, 54% indicated a high likelihood of PCOS, 34% moderate, and 12% low. Irregular periods and excessive hair growth were reported by 53% and 59% of participants, respectively. The study reveals significant correlations among various symptoms of Polycystic Ovary Syndrome (PCOS). Irregular periods positively correlated with increased facial hair growth (r = .356, p < 0.01) and waist weight gain (r = .275, p < 0.01). Heavy menstrual bleeding was strongly associated with insulin resistance (r = .355, p < 0.01) and difficulty conceiving (r = .355, p < 0.01). Notably, symptoms of insulin resistance had a perfect correlation with challenges in conceiving (r = 1.000, p < 0.01) and were positively linked to ovarian cyst diagnoses (r = 1.000, p < 0.01), highlighting the intricate interconnections among these symptoms. Discussion: Findings underscore the need for improved awareness and targeted interventions for PCOS in diverse populations, particularly in rural areas where healthcare access is limited. Further research should explore the influence of lifestyle and environmental factors on PCOS prevalence and symptomatology